Seniors' demographic correlates for motivations to enroll in degree-conferring programs in universities. Issue 6 (2nd June 2016) - Chen, Li-Kuang; Wang, Shan Tair
ABSTRACT: Policies, practices, and studies have long been focused on nonformal learning for older adults as if this were the only learning context for grey populations. In fact, today more elderly adults participate in degree-conferring programs. It is important to explore why formal learning environments attract the elderly. Therefore, the purpose of this study was to explore relationships between demographic characteristics and motivations of older adults who enroll in degree-conferring programs in higher education including undergraduate, master's, and doctoral programs in Taiwan. A total of 287 questionnaires filled out by students aged 60 and above were analyzed. The data showed that (a) The demographic characteristics of this group were dissimilar to those of elder learners in nonformal settings. Those who enrolled in degree-conferring higher education programs were predominantly male, young-old, and still employed. (b) The first five important motivations for elder adults enrolling in degree-conferring programs in universities were pursuing and updating knowledge and skills, fitting in with job-related needs and competitions, achieving a life goal, keeping abreast of social changes, and gaining a degree. (c) Retirement status and age predict enrollment motivations. This study enriches our understanding of heterogeneity of elderly learners and provides evidence to make more inclusive policies for elder education. More systematic learning with long-term and intensive requirements, such as enrolling in universities, is needed and desired by some older adults. The roles of higher education in promoting elder learning should be further discussed, addressed, and created.